2022
DOI: 10.1002/pi.6394
|View full text |Cite
|
Sign up to set email alerts
|

Effects of applied voltage on the morphology and phases of electrospun poly(vinylidene difluoride) nanofibers

Abstract: Electrospinning is a simple and flexible process in continuous fiber fabrication. We investigate the effect of applied voltage on morphology and phases of poly(vinylidene difluoride) nanofibers obtained using the electrospinning technique. Quantitative and qualitative analyses were performed employing multiple characterizations such as Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD) and high-resolution transmission electron microscopy (HRTEM). The fiber diameter, affected by the spinnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
(72 reference statements)
1
12
0
Order By: Relevance
“…This is because with the continuous increase in voltage (greater than 18 kV), the flow rate also gradually increases, the evaporation time of the solvent is shortened, and the effective stretching of the NFs is reduced. The effect of voltage on the crystalline phase transition was also confirmed in the work of Nugraha et al [ 87 ], and the change in β phase is a key factor affecting the piezoelectric properties of PVDF.…”
Section: Preparation Of Pvdf Nfs By Electrospinningmentioning
confidence: 55%
See 1 more Smart Citation
“…This is because with the continuous increase in voltage (greater than 18 kV), the flow rate also gradually increases, the evaporation time of the solvent is shortened, and the effective stretching of the NFs is reduced. The effect of voltage on the crystalline phase transition was also confirmed in the work of Nugraha et al [ 87 ], and the change in β phase is a key factor affecting the piezoelectric properties of PVDF.…”
Section: Preparation Of Pvdf Nfs By Electrospinningmentioning
confidence: 55%
“…When the voltage gradually increases, the large surface aperture becomes elliptical and the grooves become more numerous because the Taylor cone is stretched more rapidly, and the roughness decreases because it is less affected by the buckling instability, as shown in Figure 4 (1). In addition, the PVDF fiber under high voltage is more uniform, and the crystallinity of PVDF is improved [ 87 ]. In this process, the polymer solution is stretched to produce β phase due to the effect of the electric field.…”
Section: Preparation Of Pvdf Nfs By Electrospinningmentioning
confidence: 99%
“…74 As consistent with previous findings, all samples exhibited weak indications of γ-phase within the 1225-1230 cm −1 band. [74][75][76][77] Although all results showed the appearance of γ-phase formation, only in samples with 1% BT rods could the γ-phase formation be calculated. The result shows that adding 1% BT rods is the optimal point for forming the γ-phase.…”
Section: Resultsmentioning
confidence: 95%
“…Nugraha et al. also studied the effect of the spinning voltage on the content of β crystals, [ 121 ] and found that increasing the voltage could increase the content.…”
Section: Structure Manipulation Of Pvdf‐based Polymers To Improve Pie...mentioning
confidence: 99%
“…Drum speed, electric field, and flow rate are the next important factors that affect the percentage of the 𝛽 phase with variations of 6.3%, 5.9%, and 5.7% in the 𝛽 content, respectively. Nugraha et al also studied the effect of the spinning voltage on the content of 𝛽 crystals, [121] and found that increasing the voltage could increase the content.…”
Section: Electrospinningmentioning
confidence: 99%